Influence of the Nonaxisymmetric Dark Halo Shape on Galaxies Outer Spiral Pattern Morphology - Butenko, Maria; Belikova, Iraida; Khokhlova, Svetlana; Kuzmin, Nikolay; Ivanchenko, Gennadiy; Ten, Anastasiya (Mathematical Physics and Computer Modeling, 2021)
The results of numerical simulations of a gaseous galactic disk rotating in an external nonaxisymmetric potential of a dark halo are presented in the article. Analysis of two models of a nonaxisymmetric dark halo, in which a gaseous galactic disk rotates, has been carried out. In the first case, the halo is nonaxisymmetric within the optical radius of the disk, where the bulk of the visible matter of the galaxy is located, including the stellar disk. The model is ineffective for the external long-lived spiral structure formation in the disk periphery due to the nonaxisymmetry of dark halo. In the second series of calculations, we have employed the model with a symmetric halo inside the optical radius and a non-axisymmetric one outside of it. The results of the simulations confirm that nonaxisymmetry in the halo matter distribution is effectively generating the global spiral pattern at the periphery of the galaxy. One may observe such spiral structures in some galaxies, mainly in the ultraviolet range. Analysis of various model parameters has showed that the value of parameter " is the primary characteristic affecting the morphology of the forming spiral pattern. This value determines the degree of nonaxisymmetry of the halo. The Le parameter introduced in this work and responsible for the formation of small-scale structures in the transition region does not significantly affect the disk periphery. Moreover, the larger the value of Le, the smoother spirals are formed. As it has shown in this work the size of the computational grid does not significantly influence on the simulation results, revealing only small-scale structures which are not the subject of current work.